Peran Badan Usaha Milik Desa Dalam Pengembangan Potensi Wisata Danau Timbang Bunga Pengantin Di Kabupaten Kuantan Singingi - Tari Mustika Indah; Zulkarnaini Zulkarnaini (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2022)
The Kuantan Singingi Regency Government made a Regional Regulation of the Kuantan Singingi Regency regarding Guidelines for the Establishment of Village-Owned Enterprises. This study aims to determine the role of Village-Owned Enterprises (VOE) in the Development of Tourism Potential of Lake Timbang Bunga Pengantin in Kuantan Singingi Regency. There are several phenomena that occur, namely, first, Village-Owned Enterprises (VOE) have not fully managed tourism, secondly, communication has not been fully good, thirdly, there is a lack of community creativity, and the fourth Village-Owned Enterprises (VOE) have not fully invited the community to develop tourism potential. The theory used is the theory of Seyadi in Ade Eka Kurniawan using four indicators of the role of Village-Owned Enterprises (VOE), namely Monitoring, Developing Potential, Realizing Development Plans, Improving Community Welfare. This research method uses qualitative research methods. The results of the study show that first, the running of the role of Village-Owned Enterprises (VOE) can develop the potential of Timbang Bunga Pengentin Lake Tourism in Kuantan Singingi Regency which can be seen from the development targets and visitors. Second, the inhibiting factors for the role of Village-Owned Enterprises (VOE) are funds or budget, community or human resources, tourism promotion and publication, and natural disasters.